A new social wasp Mischocyttarus (Kappa) gomesi spec. nov., with a discussion of its taxonomic affinities and a description of the female of M. mocsaryi (Ducke, 1909) (Hymenoptera: Vespidae, Polistinae) - Silveira, Orlando Tobias (Zootaxa, 2013)
A new species Mischocyttarus (Kappa) gomesi, spec. nov. (Brazil, Rondônia) as well as unknown female of M. (K.) mocsaryi (Ducke, 1909) (Colombia, Arauca) are described.